Keterbatasan Guru Sekolah Dasar dalam Mengajar IPA : A Literature Review - Sudarto Sudarto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to identify the limitations of elementary school teachers in teaching Natural Sciences (IPA) in the Indonesian context. This systematic literature review identifies patterns of limitations of elementary school teachers in teaching science based on 17 selected sources in the period 2016–2026. The research method used is descriptive qualitative through a systematic literature review approach with data sources from the SINTA database, Garuda, Google Scholar, and repositories. The search keywords used are “the ability of elementary school teachers to teach science” and “challenges of elementary school science teachers”. Inclusion criteria include publications in the last 10 years and focus on the competencies of elementary school science teachers. The results of the study show several main themes, namely: 1) the dominance of the lecture method (47%, 8 articles) which is characterized by monotonous learning and students tend to be passive; 2) limited use of learning media (29%, 5 articles), such as minimal use of videos and experiments; 3) lack of variety of learning models (41%, 7 articles), especially Problem-Based Learning (PBL) and experimental models; 4) weak teacher competency (24%, 4 articles), primarily due to non-science backgrounds; and 5) low mastery of TPACK (24%, 4 articles), demonstrated by limitations in the use of information and communication technology (ICT). The impact of these limitations is low student learning outcomes and increased levels of boredom in learning. The conclusion of this study indicates that systemic limitations, in the form of teacher-centered and conventional approaches, hinder the effectiveness of science learning in elementary schools. Solutions offered include PBL-based TPACK training, the use of animated media, and the implementation of simple experiments to support the transition to student-centered learning. This study recommends the need for a national program for primary school teacher professional development based on needs assessment and ongoing supervision.